2007
DOI: 10.2174/157019307779815857
|View full text |Cite
|
Sign up to set email alerts
|

Development of Core-Corona Type Polymeric Nanoparticles as an Anti-HIV-1 Vaccine

Abstract: We developed a novel technology for core-corona polymeric nanoparticles having hydrophilic polymer chains with functional groups. Polystyrene nanoparticles immobilized with the mannose-specific lectin concanavalin A could efficiently capture human immunodeficiency virus type 1 (HIV-1) particles and gp120 antigens on their surface. Since the antigen-capturing nanoparticles were capable of inducing humoral and cellular immune responses to HIV-1, they could be developed as a mucosal vaccine against HIV-1 infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…We have previously reported that antigen-carrying corecorona polystyrene NPs (PSNPs) were efficiently taken up by DCs and did enhance the immunogenicity of antigens (28,29). Intranasal immunization of mice with heat-inactivated HIV-1-capturing PSNPs demonstrated efficient production of HIV-1-specific neutralizing antibodies in the genital tract and CTL responses in the spleen (2,10).…”
mentioning
confidence: 99%
“…We have previously reported that antigen-carrying corecorona polystyrene NPs (PSNPs) were efficiently taken up by DCs and did enhance the immunogenicity of antigens (28,29). Intranasal immunization of mice with heat-inactivated HIV-1-capturing PSNPs demonstrated efficient production of HIV-1-specific neutralizing antibodies in the genital tract and CTL responses in the spleen (2,10).…”
mentioning
confidence: 99%
“…For example a new class of complex nano-structured hybrid microspheres with a raspberry-like structure can provide a unique micro/nano-environment which has found new applications in the material, chemical, medical and environmental sectors [16][17][18][19][20]. Bai et al have synthesized novel raspberry-like TiO 2 @yeast composites, which were effective photocatalysts for the degradation of dyes [21].…”
Section: Introductionmentioning
confidence: 99%